Birth Weight of Term Neonates Born to Mothers of Various Ethnic Groups in Manipal Teaching Hospital - Timilsina, Mukunda; Gauchan, Eva (Journal of College of Medical Sciences-Nepal, 2025)
Background Birth weight is a critical indicator of neonatal health, influenced by various maternal, socioeconomic, and behavioral factors. This study aimed to assess birth weight variations among term neonates born to mothers of different ethnicities at Manipal Teaching Hospital and identify maternal factors associated with neonatal weight. Methods A cross-sectional study was conducted among 71 term neonates whose birth weights were recorded within 24 hours of delivery. Data on maternal ethnicity, age, parity, antenatal care (ANC) attendance, socioeconomic status, and health behaviors were collected. Statistical analysis included one-way ANOVA and independent t-tests. Results The mean birth weight was 2.91±0.41 kg. Although differences in mean birth weight were observed across ethnic groups, these were not statistically significant (p-value=0.15). Higher birth weights were significantly associated with ≥4 ANC visits (p-value<0.01). Parity and maternal age showed non-significant trends. Conclusions While ethnicity was not a significant determinant of birth weight, modifiable maternal factors such as ANC utilization and healthy behaviors significantly influenced neonatal outcomes, highlighting the importance of targeted maternal health interventions.